Black bean (Phaseolus vulgaris L.) as a protective agent against DNA damage in mice - Azevedo, L.; Gomes, J. C.; Stringheta, P. C.; Gontijo, AMMC; Padovani, Carlos Roberto [UNESP]; Ribeiro, Lúcia Regina [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier B.V., 2003)
This study was designed to evaluate the toxicogenetic or protective effect of cooked and dehydrated black beans (Phaseolus vulgaris L.) in bone marrow and peripheral blood cells of exposed mice. The frequency of micronuclei detected using the bone marrow erythrocyte micronucleus test and level of DNA lesions detected by the comet assay were chosen as end-points reflecting mutagenic and genotoxic damage, respectively. Initially, Swiss male mice were fed with a 20% black bean diet in order to detect mutagenic and genotoxic activity. However, no increase in the frequency of bone marrow micronucleated polychromatic erythrocytes (MN PCEs) or DNA lesion in leukocytes was observed. In contrast, received diets containing 1, 10 or 20% of black beans, a clear, but not dose-dependent reduction in the frequency of MN PCEs were observed in animals simultaneously treated with cyclophosphamide, an indirect acting mutagen. Similar results were observed in leukocytes by the comet assay. Commercial anthocyanin was also tested in an attempt to identify the bean components responsible for this protective effect. However, instead of being protective, the flavonoid, at the highest dose administered (50 mg/kg bw), induced primary DNA lesion, as detected by the comet assay. These data indicate the importance of food components in preventing genetic damage induced by chemical mutagens, and also reinforce the role of toxicogenetic techniques in protecting human health. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: anthocyanin; black beans; comet assay; genotoxicity; mutagenicity; micronucleus; Phaseolus vulgaris L.